Treatment of murine pulmonary blastomycosis with SCH 39304, a new triazole antifungal agent. - Sugar, A M (1990)
SCH 39304, a broad-spectrum azole derivative, was evaluated in an experimental mouse model of blastomycosis pneumonia. Five days after being inoculated with Blastomyces dermatitidis, infected mice were treated with either oral SCH 39304, fluconazole, or intraperitoneal amphotericin B. A dose response protective effect was observed with SCH 39304 at 5 to 100 mg/kg of body weight per day, with 5 mg of SCH 39304 per kg per day providing activity similar to that of 100 mg of fluconazole per kg per day. Colony counts of yeasts in the lungs of mice sacrificed while on therapy with SCH 39304 were consistently below those of controls, and several lungs were sterile. We conclude that SCH 39304 is effective in murine blastomycosis treatment and deserves to be evaluated in the treatment of human blastomycosis.